Genetic characterization of clinical and environmental Vibrio parahaemolyticus from the Northeast USA reveals emerging resident and non-indigenous pathogen lineages - Xu, Feng; Ilyas, Saba; Hall, Jeffrey A.; Jones, Stephen H.; Cooper, Vaughn S.; Whistler, Cheryl A. (Frontiers in Microbiology, 2015)
Gastric infections caused by the environmentally transmitted pathogen, Vibrio parahaemolyticus, have increased over the last two decades, including in many parts of the United States (US). However, until recently, infections linked to shellfish from the cool northeastern US waters were rare. Cases have risen in the Northeast, consistent with changes in local V. parahaemolyticus populations towards greater abundance or a shift in constituent pathogens. We examined 94 clinical isolates from a period of increasing disease in the region and compared them to 200 environmental counterparts to identify resident and non-indigenous lineages and to gain insight into the emergence of pathogenic types. Genotyping and multi-locus sequence analysis of clinical isolates collected from 2010-2013 in Massachusetts, New Hampshire and Maine revealed their polyphyletic nature. Although 80% of the clinical isolates harbored the trh hemolysin either alone or with tdh, and were urease positive, 14% harbored neither hemolysin exposing a limitation for these traits in pathogen detection. Resident sequence type (ST) 631 strains caused seven infections, and show a relatively recent history of recombination with other clinical and environmental lineages present in the region. ST34 and ST674 strains were each linked to a single infection and these strain types were also identified from the environment as isolates harboring hemolysin genes. Forty-three ST36 isolates were identified from the clinical collection, consistent with reports that this strain type caused a rise in regional infections starting in 2012. Whole-genome phylogenies that included three ST36 outbreak isolates traced to at least two local sources demonstrated that the US Atlantic coastal population of this strain type was indeed derived from the Pacific population. This study lays the foundation for understanding dynamics within natural populations associated with emergence and invasion of pathogenic strain types in the region.